Spatial and Temporal Distribution of Dolichoderus Thoracicus Smith in a Cocoa-Coconut Agroecosystem - Liew, Voon kheong (1999)
Cocoa, an important crop in Malaysian agriculture is subjected to infestation by a number of insect species the most important of which is the cocoa pod borer, Conopomorpha cramerella Snellen. The black cocoa ant, Dolichoderus thoracicus is found to be effective in controlling this pest. The abundance of nesting sites is crucial in the establishment of this ant. Coconut palms afford a great deal of nesting sites in the crown and spadices. A large number of ants also nests in artificial cocoa leaf-litter nests which basically comprises of a plastic bag (3 1 x 45 cm) stuffed with dry cocoa leaves. The ants also nests in the cocoa canopy, between two cocoa leaves that overlapped forming a leaf nest. The population size of the ant in the three types of nests on a per hectare basis should be compared to determined the more important nesting site. Hence the objective was to a) study the distribution of the ants in the spadices of coconut crowns, cocoa canopy and artificial cocoa leaf-litter nest b) study the effects of time and amount of cocoa leaf-litter on the size of ant population in the artificial nest and c) determine the nest site preference of D. thoracicus in the canopy of cocoa trees. A sampling technique using a pipette fitted with a modified tip was developed to estimate the number of ants and its brood in various types of nests. The end of the pipette tip was cut to make an opening with a diameter of 4.2 mm. Results showed that taking seven aliquots of 3 ml per aliquot gave the best estimate for adults and total number of individuals. Samples of all three types of nests i.e. spadices, artificial nests and cocoa leaf nests were obtained and the number of adults and brood on a per hectare basis estimated. There were significantly more ants in the artificial nests compared to the other two types of nests. The nest site preference of the ant in relation to canopy strata was examined. The ants prefered to live in nests placed at the top and bottom strata of the canopy. Artificial nests were set up on the cocoa trees and the change in population size of the ants in the nests over time was observed. The ants colonized the nests after two months with the population reaching a maximum of about 20 x 1 04 individuals in about five months. In another experiment, 1 75 , 3 50, 525 and 700g of dry cocoa leaves were placed in plastic bags measuring 3 1 x 45 cm. All four treatments were placed on a cocoa tree. After five months, it was found that the bag with 3 50g of dry leaves had significantly more ants compared to the other three nests. This study shows the potential of the artificial cocoa leaf-litter nest in the establishment of the black cocoa ant especially in a monococoa agroecosystem. In Malaysia where the cocoa pod borer poses a serious problem, the use of the artificial nest will help in the establishment of the ants and thus leading to the control of the most dangerous insect pest of cocoa.